Finding the Kool Mixx: how Brown & Williamson used music marketing to sell cigarettes. Issue 5 (22nd September 2006) - Hafez, Navid; Ling, Pamela M
Abstract : Objective: To describe the history of Kool's music-themed promotions and analyse the role that music played in the promotion of the brand. Methods: Analysis of previously secret tobacco industry documents, legal documents, and promotional materials. Results: Brown & Williamson started Kool sponsorship of musical events in 1975 with Kool Jazz concerts. Music was considered to be an effective marketing tool because: (1) music helped consumers make emotional connections with the brand; (2) music concerts were effective for targeted marketing; (3) music tied together an integrated marketing campaign; and (4) music had potential to appeal widely to a young audience. Brown & Williamson's first music campaigns successfully targeted young African-American male audiences. Subsequent campaigns were less effective, exploring different types of music to achieve a broader young adult appeal. Conclusions: This case study suggests Brown & Williamson used music most successfully for targeted marketing, but they failed to develop a wider audience using music because their attempts lacked consistency with the Kool brand's established identity. The 2004 "Kool Mixx" campaign both returned to Brown & Williamson's historic practice targeting young African-American males, and also exploited a musical genre with much more potential to bring Kool more universal appeal, as hip-hop music is increasingly popular among diverse audiences. Tobacco control efforts led by African-American community activists to oppose these marketing strategies should continue; expanding these coalitions to include the hip-hop community may further increase their effectiveness.